TESTING THE RELATIONSHIP BETWEEN EXCHANGE RATE AND STOCK PRICE IN THE ASEAN COUNTRIES - Dwipraptono Agus Harjito (Universitas Islam Indonesia, 2009)
The aim of this paper is to investigate the statistical relationship between stock prices and exchange rates in ASEAN from 1993–2006. Using Engle-Granger test, it finds that the re-lationship between stock prices and exchange rates is characterized by a feedback system, with Singapore Dollar as the dominant exchange rate. Johansen co-integration test finds that all of the stock prices and exchange rates are co-integrated. The results are supported by Vector Autoregression and Vector Error Correction Models. With respect to the relationship between stock prices and exchange rates, the results are inconclusive. The causality mostly runs from exchange rates to stock prices.